2016
DOI: 10.1016/s1001-6058(16)60609-1
|View full text |Cite
|
Sign up to set email alerts
|

Pelton turbine: Identifying the optimum number of buckets using CFD

Abstract: A numerical case study on identifying the optimum number of buckets for a Pelton turbine is presented. Three parameters: number of buckets, bucket radial position and bucket angular position are grouped since they are found to be interrelated. By identifying the best combination of the radial and angular position for each number of buckets it is shown that reduction in the number of buckets beyond the limit suggested by the available literature can improve the runner efficiency and be beneficial from the manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 16 publications
0
29
0
1
Order By: Relevance
“…Since this study was parametric, no theoretical suggestion for calculating the optimum number of blades has been made. For a Pelton runner, e.g., Zidonis et al [27], the optimum number of buckets can be estimated using the ratio of water jet diameter and runner diameter. The main design consideration in doing so is to avoid the jet interference with the buckets (due to a high number buckets) as well as the loss of jet (due to a low number of buckets) [27].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since this study was parametric, no theoretical suggestion for calculating the optimum number of blades has been made. For a Pelton runner, e.g., Zidonis et al [27], the optimum number of buckets can be estimated using the ratio of water jet diameter and runner diameter. The main design consideration in doing so is to avoid the jet interference with the buckets (due to a high number buckets) as well as the loss of jet (due to a low number of buckets) [27].…”
mentioning
confidence: 99%
“…For a Pelton runner, e.g., Zidonis et al [27], the optimum number of buckets can be estimated using the ratio of water jet diameter and runner diameter. The main design consideration in doing so is to avoid the jet interference with the buckets (due to a high number buckets) as well as the loss of jet (due to a low number of buckets) [27]. This design principle is unlikely to carry over to crossflow turbines because the optimization of N b is likely to result from a balance between reduction in flow separation and increasing boundary layer blockage as N b increases.…”
mentioning
confidence: 99%
“…To reduce the timescale only 2 consecutive buckets were used to represent the torque of the whole runner and the individual effect of 11 design parameters were compared and discussed. The CFX case study was continued further using the same set-up to investigate the optimum number of buckets [75]. Numerical results validated experimentally showed that reducing the number of buckets beyond the limit suggested by the previously available literature can improve the runner efficiency and be beneficial from the manufacturing complexity and cost point of view.…”
Section: Pelton Runnermentioning
confidence: 99%
“…Low-scale pelton turbines are given a limit of 10 m minimum head, 0.5 ℓ / s water flow, a minimum output power of 0.1 kW and a minimum jet diameter of 4 mm [7]. The working principle of pelton turbines is to convert gravitational potential energy into kinetic energy, where the velocity of the water jet increases and hits the bucket turbine then converts it to mechanical energy (shaft rotation), which is quickly converted to electrical energy [5] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Available literature usually concentrates on the analysis or optimization of distributor design, injectors, bucket geometry or turbine casings. However, there is not much research published in terms of optimum bucket numbers [7].…”
Section: Introductionmentioning
confidence: 99%